Analisis Bahasa Tulis Aksara Arab pada Anak dengan Gangguan Disleksia: Kajian Psikolinguistik - Siti Marya Ulpah; Tatang (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This research was conducted because there are problems with written Arabic script in children with dyslexia which has the potential to affect language abilities. This research aims to find out, understand, explain and describe the forms of written Arabic script in children with dyslexia. This research uses descriptive qualitative research. The subject of this research was RSK, a 10-year-old child who was in the fifth grade of elementary school. The data source for this research comes from written language documentation of the research subjects. Data collection techniques used in this research are interviews, documentation and observation. Research data was analyzed using data reduction techniques, data presentation, data verification and conclusions. The results of this research are that dyslexia in children causes various errors in children's written language. These errors include inversion (writing backward), writing the wrong period, substitution (replacing letters), and deletion (removing letters). This error occurs in hijaiyah letters which have similar visual shape and sound proximity to other hijaiyah letters.